Studies on the effects of light energy and temperature on Trifolium subterraneum L. and Trifolium hirtum All. in a natural environment - Wicht, J. E.(John Edward) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1970.